2002
DOI: 10.1086/339718
|View full text |Cite
|
Sign up to set email alerts
|

Altered Rainfall Patterns, Gas Exchange, and Growth in Grasses and Forbs

Abstract: Although the potential for increased temperature is the primary and best-studied aspect of anthropogenic climate change, altered rainfall patterns, increased storm intensity, and more severe droughts are also predicted in most climate-change scenarios. We altered experimentally the rainfall regime in a native tallgrass prairie in northeastern Kansas and assessed leaf-level physiological activity and plant growth responses for C 3 and C 4 plant species. Our primary objective was to contrast the importance of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
85
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(96 citation statements)
references
References 51 publications
(49 reference statements)
9
85
2
Order By: Relevance
“…A deeper root system and clonal integration for C. dactylon (through both stolons and rhizomes), and especially for P. alba (Magyar 1933, Forde 1966, Krízsik & Körmöczi 2000 may provide a greater ability for these species to reach water resources in deeper soil layers and exploit spatial environmental heterogeneity. Consistently, in other studies in arid or semiarid habitats, shallow rooted plants were found to be more constrained by severe drought than deep rooted species (Schwinning et al 2005, Wertin et al 2015), however such difference can be buffered physiologically (Fay et al 2002). In our experiment, the effective source-to-sink assimilate transport of C. dactylon (Forde 1966) and the production of root suckers of P. alba may reduce end-product limitation on photosynthesis.…”
Section: Responses To Precipitationsupporting
confidence: 91%
See 2 more Smart Citations
“…A deeper root system and clonal integration for C. dactylon (through both stolons and rhizomes), and especially for P. alba (Magyar 1933, Forde 1966, Krízsik & Körmöczi 2000 may provide a greater ability for these species to reach water resources in deeper soil layers and exploit spatial environmental heterogeneity. Consistently, in other studies in arid or semiarid habitats, shallow rooted plants were found to be more constrained by severe drought than deep rooted species (Schwinning et al 2005, Wertin et al 2015), however such difference can be buffered physiologically (Fay et al 2002). In our experiment, the effective source-to-sink assimilate transport of C. dactylon (Forde 1966) and the production of root suckers of P. alba may reduce end-product limitation on photosynthesis.…”
Section: Responses To Precipitationsupporting
confidence: 91%
“…This allows making investigations on one or a few, mostly dominant species as representatives of functional types. Different plant functional types, according to their life form, phenology, vegetative growth, rooting pattern or photosynthesis type, often respond differently to natural or experimentally simulated climatic stresses (Mamolos et al 2001, Fay et al 2002, Xia & Wan 2013, Wertin et al 2015, which may result in changes in the dominance structure and composition of the community (Alward et al 1999, Zavaleta et al 2003.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dreesen et al, 2012;Carón et al, 2014a) and of soil moisture variability (e.g. Fay et al, 2002Fay et al, , 2012 on growth. However, it is possible that the high organic matter content (20%) of the potting soil used in this experiment induced a high water retention capacity, therefore, irrespective of the treatments applied, the seedlings never experienced strong drought stress related to the differences in watering frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Precipitation frequency may change separately from rainfall totals when the total amount of rainfall over a certain period remains constant, but the number of rainfall events decreases and the precipitation amount in each rainfall event increases. Some of the few available studies on plants have shown that reduced rainfall frequencies can increase productivity, decrease root-to-shoot ratios or affect leaf senescence in grassland species (Fay et al, 2003(Fay et al, , 2002Schneider et al, 2014). Yet, more research is urgently needed to better understand the effect of changes in precipitation frequency on other plant growth parameters, functional groups, and ecosystems (Schneider et al, 2014).…”
Section: Introductionmentioning
confidence: 99%